The Use of Dwarf Octopus (Octopus joubini) As A Model for Hands-On Research Experience in Comparative Psychology - Wincheski, Riley; Stauch, Kiri; Grossner, Laura M; Gruenes, Stella; Lewis, William A.; Abramson, Charles I (International journal of comparative psychology, 2024)
The Laboratory of Comparative Psychology and Behavioral Biology at Oklahoma State University has been developing comparative psychology teaching exercises for over 30 years. In this paper, we provide suggestions for using the dwarf octopus (Octopus joubini) to teach students about the importance of observation, and the relationship of observation in the creation of ethograms and experimental design. Throughout this paper, students learn how to properly make an observation of a novel animal, create an ethogram, and conduct an experiment. We present a sample observation activity and three additional experiments, during which students will observe and record behaviors and environmental conditions. Students learn saltwater tank upkeep, time management, creation and coding of operational definitions, attention to changes in animal behavior, and the experimental process. These observation studies allow students to observe and record behavioral data to understand comparative psychology and experimental design.